Accident & emergency theory into practice - Dolan, Brian 1963-; Holt, Lynda (Baillière Tindall Elsevier, 2013)
This edition shows nurses why they are doing what they do, rather than just how, for a range of A&E conditions. It has sections that cover potential problem areas, such as paediatrics and treating the mentally ill A&E patient. A basic A&P section is included so even the most experienced nurse can refresh their knowledge.